ANALISIS MODEL TARIKAN PERGERAKAN KENDARAAN MENUJU KAWASAN EKONOMI KHUSUS (KEK) WISATA TANJUNG GUNUNG KABUPATEN BANGKA - Indra Gunawan; Boy Dian Anugra Sandy (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
During the New Normal period of the Covid-19 pandemic, activities in the economic, social, and cultural sectors began to resume activities. Likewise, activities in the tourism sector which have begun to be active again, supported by land, sea, and air transportation modes have also begun to be active again. This is in accordance with the President's desire to accelerate economic recovery during the Covid-19 pandemic. This effort is also one of the commitments of the Provincial Government of Bangka Belitung Islands to focus on developing tourism sector. There are several Special Economic Tourism Zones in the Province of Bangka Belitung Islands, one of which is Tanjung Gunung Tourism. The purpose of this study is to create a model that is used to calculate the magnitude of the attraction of vehicle movement and to identify and analyze the factors that influence to obtain a model of attraction for the movement of vehicles and visitors in tourist area of ​​Tanjung Gunung, Central Bangka Regency. There are 3 tourist destinations in this area, namely Pan Semujur Beach, Angsa Emas Hill, and Tapak Antu Beach. Data obtained by doing a correlation test and then doing a regression analysis to get the equations model. The independent variables reviewed included: prayer room (X1), bath room (X2), huts area (X3), dining area (X4), and ​​parking area (X5). From the regression analysis, it was found that a good model for pulling movement is: Y = -37.423+0.7203X4 with a coefficient of determination (R2) = 0.99. total dining area (X4).